Alternative therapies for PTSD : the science of mind-body treatments - Motta, Robert W. (American Psychological Association, 2020)
"Traditional psychological treatments that are most often used to treat PTSD, including cognitive behavioral therapy and prolonged exposure therapy, involve revisiting past traumas, which can cause intense anxiety for clients and often leads to treatment dropout. This book surveys promising alternatives that are much easier for trauma survivors to tolerate and have demonstrated effectiveness in building coping mechanisms and reducing PTSD symptoms. The author, Robert Motta, draws from his own professional expertise as a clinician and from his personal experiences as a veteran seeking effective, accessible methods of treating his own PTSD. He summarizes what is known-as well as what is still unknown or unproven-along with other strengths and limitations of various nontraditional approaches, including mindfulness meditation, yoga, acupuncture, animal and nature-assisted therapies, emotional freedom techniques, and MDMA-assisted psychotherapy. These treatments are appropriate for clients regardless of their trauma history, whether it be war, rape, childhood abuse, or a car accident. Clinical vignettes provide practical insights for implementing these interventions with individuals of various ages and backgrounds"--